Comparison of Nonstress Test and Light stimulation Test and their correlation with fetal outcome - Khanam, Deeba; Bano, Imam (International Journal of Medical Research and Review, 2015)
Introduction: Non Stress Test serves an important function in assessment of fetal wellbeing, but false positive results limit its role. Light stimulation stimulates the fetus, speeds up the test and catalyses its rate limiting step. This study has compared simple Non Stress Test and Light stimulation test and there correlation with various fetal outcomes. This study helps us to assess whether light stimulation be used as a better alternative or an adjunct to traditional Nonstress test. Material and Methods: A total of 220 patients above 34 weeks of pregnancy were taken.110 pts underwent 20 minutes of Nonstress test and 110 underwent Halogen light stimulation which was given transabdominally for 10 seconds and it was repeated every 10 minutes for a maximum up to three times. This allocation was done randomly. Non reactive Nonstress test were then stimulated with Halogen light. Results: The test showed that sensitivity of Nonstress test is greater than Light stimulation test, but specificity, positive predictive value, and negative predictive value is lesser than Light stimulation test .Out of 36 Non reactive NSTs after stimulation with light 18 became reactive. Conclusion Nonstress test is considered as a screening test and Light stimulation test can be used as an adjunct to Nonstress test as it decreases the number of false positive results and increases the specificity of the test. Clinical outcomes are more closely related with LST, but more studies are required to arrive at the final conclusions.